Biophilic urbanism: a case study on Singapore - Newman, Peter (Routledge, 2014)
This paper outlines the characteristics of an emerging new planning paradigm called biophilic urbanism by detailing a case study of Singapore, which, over a number of years, has demonstrated how high density does not have to mean reduced natural systems. The paper looks at how biophilic urbanism works to improve natural systems between buildings and on the facades and rooftops of buildings.